Health outcomes of only children across the life course: An investigation using Swedish register data. (2nd January 2023) - Keenan, Katherine; Barclay, Kieron; Goisis, Alice
Abstract : Only children (with no full biological siblings) are a growing subgroup in many high-income settings. Previous studies have largely focused on the short-term developmental outcomes of only children, but there is limited evidence on their health outcomes. Using Swedish population register data for cohorts born 1940–75, we compare the health of only children with that of children from multi-child sibling groups, taking into account birth order, family size, and presence of half-siblings. Only children showed lower height and fitness scores, were more likely to be overweight/obese in late adolescence, and experienced higher later-life mortality than those with one or two siblings. However, only children without half-siblings were consistently healthier than those with half-siblings, suggesting that parental disruption confers additional disadvantages. The health disadvantage was attenuated but not fully explained by adjustment for parental characteristics and after using within-family maternal cousin comparison designs.